2014
DOI: 10.1007/s13204-014-0368-4
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation of odorous 2-mercaptobenzoxazole through zinc oxide/hydroxyapatite nanocomposite

Abstract: In this study, ZnO/HAP nanocomposite with excellent photocatalytic activities was successfully synthesized by sol-gel method and used for degradation of 2-mercaptobenzoxazole (MBO) as model of odorous mercaptan compound in water. To optimize the performance of ZnO/ HAP photocatalytic capabilities, ZnO/HAP loading (0.05-0.3 g/L), irradiation time (15-180 min), pH (3-11) and initial concentration of MBO (10-100 ppm) were investigated. At neutral pH of 7, the highest amount of the MBO (99.45 %) was degraded by Zn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…To highlight the potential catalytic efficiency of green ZnO NPs toward environmental remediation and avoid the water pollution; photodegradation experiments of DBT aqueous solution was investigated under UV light irradiation in a homemade batch-type photoreactor which has been previously described in detail by our research group 37 . Under optimum preparation conditions (see Supplementary), typically 20 mL sample of wastewater comprising 0.01 g of nanophotocatalyst and 10 ppm of DBT with neutral pH of 7 was placed into the reactor.…”
Section: Resultsmentioning
confidence: 99%
“…To highlight the potential catalytic efficiency of green ZnO NPs toward environmental remediation and avoid the water pollution; photodegradation experiments of DBT aqueous solution was investigated under UV light irradiation in a homemade batch-type photoreactor which has been previously described in detail by our research group 37 . Under optimum preparation conditions (see Supplementary), typically 20 mL sample of wastewater comprising 0.01 g of nanophotocatalyst and 10 ppm of DBT with neutral pH of 7 was placed into the reactor.…”
Section: Resultsmentioning
confidence: 99%
“…Intermolecular hydrogen bonding occurs between OH‐2 and the neighboring O‐6 of the D‐glucopyranosyl residues on different molecules, while, an intramolecular hydrogen bonding usually takes place between OH‐6 and the adjacent hemiacetal oxygen atom of the D‐glucopyranosyl residues . Hence, following our previous studies on NPs , in this communication, we explored a facile, green, low‐cost, and homemade route synthesis of durable magnetite NPs via starch‐rich potato extract, without any additives such as reducing agent, acids, and organic solvents. According to the literature review, phytosynthesis of pure magnetite NPs was reported for the first time, utilizing starch‐rich potato extract as a stabilizing and reducing agent.…”
Section: Introductionmentioning
confidence: 99%
“…without illumination) and absorbance aftert time illumination provided the % of photodegradation which ultimately disclosed the efficiency of the composite. Following equation (Buazar et al 2015;Ahmed et al 2011) was used to calculate the % of degradation.…”
Section: Treatment Of Mb Using Hap-tio 2 -Zno Composite Under Illuminmentioning
confidence: 99%